Development of an Integrating Ethnoscience Module in Project-Based Learning to Enhance the Pedagogical Competence of Elementary Teacher Education Students - Nasharuddin; Muhammad Amin Said; Amri Amal; Andi Adam Mahendra (Jurnal Penelitian Pendidikan IPA, 2025)
Improved the quality of science education in elementary teacher training requires the development of instructional modules that are both contextual and culturally responsive. This study was conducted to design, implement, and evaluate a Project-Based Learning (PjBL) module integrated with ethnoscience to enhance the pedagogical competence of Elementary School Teacher Education students. Using a 4D development model (Define, Design, Develop, and Disseminate), the study included expert validation and user practicality testing. The module contextualized scientific content, particularly the concept of heat and temperature, using local cultural practices such as traditional palm sugar processing. Validation results indicated high feasibility scores in the didactic (94.00%), construction (96.00%), and visual aspects (98.33%) categories, while the practicality test produced an average score of 92.00%. Moreover, inferential insights from the evaluation revealed statistically significant improvements in learners' conceptual understanding (N-gain score of 0.80). The findings demonstrated that integrating ethnoscience into project-based modules not only deepened students’ comprehension of scientific principles but also fostered their ability to design meaningful, culturally relevant instruction. This research offers a valuable contribution to teacher education by presenting a validated instructional model that bridges scientific theory and local wisdom, promoting contextualized and engaging science learning. The module provides a scalable framework for future research and application across diverse educational and cultural settings.